2022
DOI: 10.32942/osf.io/4nv3w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are we underestimating the ecological and evolutionary effects of warming? Interactions with other environmental drivers may increase species vulnerability to high temperatures

Abstract: Warming, the most prominent aspect of global environmental change, already affects most ecosystems on Earth. In recent years, biologists have increasingly integrated the effects of warming into their models by capturing how temperature shapes their physiology, ecology, behavior, evolutionary adaptation, and probability of extirpation/extinction. The more physiologically-grounded approaches to predicting ectotherms’ responses use thermal performance curves (TPCs) obtained by measuring species performance (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Others have previously proposed reaction norms of vital rates as a starting point to merge physiology with multiple driver research (Collins et al, 2022; Harley et al, 2017; Litchman & Thomas, 2022; Pirotta et al, 2022). Litchman and Thomas (2022) reviewed the literature on phytoplankton growth and found that all reviewed global change drivers can influence the shape of the TPCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have previously proposed reaction norms of vital rates as a starting point to merge physiology with multiple driver research (Collins et al, 2022; Harley et al, 2017; Litchman & Thomas, 2022; Pirotta et al, 2022). Litchman and Thomas (2022) reviewed the literature on phytoplankton growth and found that all reviewed global change drivers can influence the shape of the TPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Others have previously proposed reaction norms of vital rates as a starting point to merge physiology with multiple driver research (Collins et al, 2022; Harley et al, 2017; Litchman & Thomas, 2022; Pirotta et al, 2022). Litchman and Thomas (2022) reviewed the literature on phytoplankton growth and found that all reviewed global change drivers can influence the shape of the TPCs. Collins et al (2022) then made the point that response curves for phytoplankton can only be produced with many driver levels, including unrealistic levels that are not expected to happen in nature.…”
Section: Introductionmentioning
confidence: 99%